Analisis Strategi Pemasaran Daily Routine Coffee Bandung - Saptadinata, Abi; Ritasari, Rd Rita; Sulistyowati, Reni; Kusmayadi; Nurrizki, Muhammad Ghifari (Politeknik Sahid, 2022)
West Java is one of the provinces in Indonesia that has the potential for business people to develop a form of business. One of the business fields that have significant opportunities is culinary tourism. The coffee shop is a business mushrooming with the increasing trend of coffee shops. This research is tasked with knowing the marketing strategy of Daily Routine Coffee Bandung during the COVID-19 pandemic to increase sales at Daily Routine Coffee. The research method is done using qualitative research methods with a descriptive approach. The unit of analysis used in this final project research is Daily Routine Coffee in Bandung. This business is a business engaged in the F&B sector. The sample will be used in the form of sales trend data and environmental analysis of internal and external company strategies at the Daily Routine Bandung coffee shop. Based on the research results using Marketing Mix Analysis, a suitable strategy to be implemented is an Intensive Strategy (market penetration, market development, and product development). Based on IFAS & EFAS analysis, a value of 3.68 is obtained for external factors, and internal factors is obtained at 3.52. Thus, internal factors are more vital than external factors in the accepted trend. IFAS/EFAS analysis is in quadrant 1 (Grow and Build). Therefore, this describes a very favorable situation